2018
DOI: 10.1002/1873-3468.13041
|View full text |Cite
|
Sign up to set email alerts
|

Structural and enzymatic analyses of Anabaena heterocyst‐specific alkaline invertase InvB

Abstract: Anabaena sp. PCC 7120 encodes two alkaline/neutral invertases, namely InvA and InvB. Following our recently reported InvA structure, here we report the crystal structure of the heterocyst-specific InvB. Despite sharing an overall structure similar to InvA, InvB possesses a much higher catalytic activity. Structural comparisons of the catalytic pockets reveal that Arg430 of InvB adopts a different conformation, which may facilitate the deprotonation of the catalytic residue Glu415. We propose that the higher ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
9
2
1
Order By: Relevance
“…It was recently reported that three amino acid residues (D188, E414, and Arg430) were found to be associated with catalytic activity, established in crystal-structure comparison and enzymatic assays of CINs (InvA and InvB), which is isolated from the cyanobacterium Anabaena [22,23]. In the current paper, these three conserved residues were also observed in all CIN genes within five Solanum plants on the basis of sequence alignment, except that SmCIN08 was missing D188, and SmCIN07 lacked the E414 and Arg430 residues ( Figure 2 and Table S1).…”
Section: Potential Functional Conservation: Four Key Amino Acid Residuesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently reported that three amino acid residues (D188, E414, and Arg430) were found to be associated with catalytic activity, established in crystal-structure comparison and enzymatic assays of CINs (InvA and InvB), which is isolated from the cyanobacterium Anabaena [22,23]. In the current paper, these three conserved residues were also observed in all CIN genes within five Solanum plants on the basis of sequence alignment, except that SmCIN08 was missing D188, and SmCIN07 lacked the E414 and Arg430 residues ( Figure 2 and Table S1).…”
Section: Potential Functional Conservation: Four Key Amino Acid Residuesmentioning
confidence: 99%
“…In addition, analysis of the crystal structures of CINs (InvA and InvB) in a cyanobacterium revealed overall structural similarity of InvA and InvB invertases [22,23]. They share an (α/α)6-barrel core structure composed of 12 α-helices and an insertion of three helices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, heterocysts, as a result of the photosystem switch, rely on neighboring cells to provide NADPH for the nitrogen fixation process through the oxidative pentose phosphate pathway (OPP) and to provide sucrose or glycogen to maintain their metabolism. , Two different enzymes catalyze the degradation of sucrose: sucrose synthase (SUS) and invertase (Inv). SUS can reversibly decompose sucrose into ADP-glucose or UDP-glucose and fructose, while sucrose invertase (Inv) can unidirectionally catalyze the hydrolysis of sucrose into fructose and glucose . Inv plays a major role when cells have high carbon and energy needs .…”
Section: Discussionmentioning
confidence: 99%
“…A catálise da hidrólise irreversível da sacarose libera glicose e frutose (XIE et al, 2018), que podem ser utilizadas pelos microrganismos durante a fermentação alcoólica para produzir etanol (TRAN et al, 2020). Devido a isso, é considerada como enzima chave do metabolismo do açúcar nas uvas (HOVASSE et al, 2016).…”
Section: Invertaseunclassified